Performance modeling and simulation of microstrip dipole array antenna for WLAN application - Soh, Ping Jack; Amir Razif Arief, Jamil Abdullah; Aiza, M. M.; Azremi, Abdullah Al Hadi; Abd Aziz, M. Z A (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org